2020
DOI: 10.1088/2053-1591/ab6c9c
|View full text |Cite|
|
Sign up to set email alerts
|

Spinel zinc ferrite nanoparticles: an active nanocatalyst for microwave irradiated solvent free synthesis of chalcones

Abstract: A profoundly effective magnetically recoverable nano zinc ferrite nanocatalyst was fabricated by means of sol-gel auto ignition strategy. The synthesized nanocatalyst has been completely portrayed by standard techniques for structural, morphological, compositional, surface, magnetic, dielectric, optical and photoluminescence properties individually. The x-ray diffraction pattern affirmed the arrangement of cubic spinel structure with an average crystallite size of 21 nm. FE-SEM images uncovered the circular mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(46 citation statements)
references
References 73 publications
(73 reference statements)
1
37
0
Order By: Relevance
“…Fig.3 is the infrared spectrum of the sample synthesized with different input powers at 50℃. Each sample has an obvious absorption peak in 581-584cm -1 , which is related to the vibration of octahedral metal ion oxygen complex [33] , [46] . All samples presented FTIR stretching bands at about 410 cm -1 (also due to Me-O stretching) [47] .…”
Section: Resultsmentioning
confidence: 99%
“…Fig.3 is the infrared spectrum of the sample synthesized with different input powers at 50℃. Each sample has an obvious absorption peak in 581-584cm -1 , which is related to the vibration of octahedral metal ion oxygen complex [33] , [46] . All samples presented FTIR stretching bands at about 410 cm -1 (also due to Me-O stretching) [47] .…”
Section: Resultsmentioning
confidence: 99%
“…In the field of nanomagnetism, the spinel ferrites are important materials because they exhibit unusual magnetic and electrical properties in comparison with their bulk counterpart [ 4 , [10] , [11] , [12] ]. Nanocrystalline spinel ferrites have been demonstrated as useful material for hyperthermia [ 13 , 14 ], detection of COVID-19 [ 15 ], visible light-enabled photodegradation [ 16 ] and, the catalyst for the synthesis of chalcones [ 17 ]. The molecular formula of spinel-type ferrite is MFe 2 O 4 (M = Co, Ni, Mn, Mg, or other divalent cations) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the prepared silica aerogel samples the physisorption isotherms were found that of type IV [32]. According to IUPAC classification, hysteresis loops, mesoporous materials consistent with type IV hysteresis loops [34][35][36]. The obtained isotherms plots of silica aerogel with different pH values indicate mesoporous (2-50 nm) size.…”
Section: Resultsmentioning
confidence: 73%